Treatment of taeniasis with Puag-Haad: A crude extract of Artocarpus lakoocha Wood - P. Charoenlarp (2018)
Thirty-nine patients with tapeworm infection were treated with five grams of crude aqueous extract of Artocarpus lakoocha wood, 'Puag-Haad'. Seven of them vomited the drug immediately. Of the 32 patients, segments with scolices of Taenia saginata and of Taenia solium were recovered from 24 and 2 patients, respectively. The side effects were vomiting and nausea.